TANDA EMOSI TROPES SYMBOL PADA KOMIK INDONESIA PASUTRI GAJE - Ni Putu Candra Lestari; Ni Putu Ira Puspita Dewi (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
This study aims to describe symbolic form of sign used to describe the emotions of Pasutri Gaje comic characters. Theoretically, this study discusses tropes symbols as additional elements whose existence has a major influence on conveying the emotions of the characters to the readers. This is a descriptive qualitative study. Apply the theory of semiotics proposed by Ferdinand de Saussure about dichotomy signifie dan significant and Pierce about triadic feature of sign. Datas sourced from picture of online comic Pasutri Gaje season 1 until episode 13 season 3. Datas is collected by observing method with recording and note-taking technique. Data were analysed by extralingual equivalent methods and comparative relational techniques. Data presented used formal and informal method. There seven kind of emotions symbol called tropes symbol used in comic. There were cross popin for angry sign, sweat drops to clumsy sign, drool to show feeling tempted, chibi to show childish side, dog ear/tail to express innocence in expecting something, blush to express feeling embarrassed, and shadow over face to show extreme anger. Tropes symbols fulfills the element of signification in accordance with the concept proposed by Pierce hence it can convey the emotional situation of character to the readers.